The utilisation of vascular limb salvage services in the assessment and management of chronic limb‐threatening ischaemia and diabetic foot ulceration: A systematic review. Issue 7 (3rd June 2020) - Nickinson, A. T. O.; Houghton, J. S. M.; Bridgwood, B.; Essop‐Adam, A.; Nduwayo, S.; Payne, T.; Sayers, R. D.; Davies, R. S. M.
Abstract: Specialist vascular limb salvage services have gained prominence as a new model of care to help overcome barriers which exist in the management of patients with chronic limb‐threatening ischaemia (CLTI) and/or diabetic foot ulceration (DFU). This systematic review aims to explore the nature of reported services, investigate their outcome in the management of CLTI/DFU, and assess the scope and quality of the evidence base to help make recommendations for future practice and research. A systematic search of MEDLINE, Embase, The Cochrane Library, Scopus and CINAHL, from 1st January 1995 to 18th January 2019, was performed. Specialist vascular limb salvage services were defined as those services conforming to the definition of "centres of excellence" within the 2019 Global Vascular Guidelines. A study protocol was registered at the International Prospective Register of Systematic Reviews (PROSPERO) (CRD42019123325). In total, 2260 articles were screened, with 12 articles (describing 11 services) included in a narrative synthesis. All services ran akin to the "toe‐and‐flow" model, with a number of services having additional core input from diabetology, microbiology, allied health professionals and/or internal/vascular medicine. Methodological weaknesses were identified within the design of the included articles and only one was deemed of high quality. The inception of services was associated with improved rates of major amputation; however, no significant changes in minor amputation or mortality rates were identified. Further research should adopt more a standardised study design and outcomes measures in order to improve the quality of evidence within the literature.